2016
DOI: 10.1016/j.jadohealth.2015.10.251
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Current and Past Binge Drinking and Systolic Blood Pressure in Young Adults

Abstract: A B S T R A C TPurpose: Heavy episodic (i.e., "binge") drinking (i.e., !five drinks/occasion) is highly prevalent among young adults; those who binge do so four times per month on average, consuming nine drinks on average on each occasion. Although it is well established that chronic heavy drinking (!two alcoholic beverages per day) increases the risk of hypertension, the relationship between binge drinking and blood pressure is not well described. Our aim was to describe the relationship between frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
(28 reference statements)
3
17
0
Order By: Relevance
“…We previously reported that young adults (18 to 25 years) with a history of binge drinking (mean of 4 years) had reduced flow‐mediated vasodilation and endothelium‐independent (nitroglycerin) dilations compared to age‐matched abstainers (Goslawski et al., ). Others have also reported that, in young adults, a binge pattern of drinking was associated with higher blood pressure (Wellman et al., ), increased carotid intimal thickness (Pletcher et al., ), and increased coronary calcification (van Trijp et al., ). These findings suggest that binge drinking may be associated with premature CV risk in young adults.…”
mentioning
confidence: 95%
“…We previously reported that young adults (18 to 25 years) with a history of binge drinking (mean of 4 years) had reduced flow‐mediated vasodilation and endothelium‐independent (nitroglycerin) dilations compared to age‐matched abstainers (Goslawski et al., ). Others have also reported that, in young adults, a binge pattern of drinking was associated with higher blood pressure (Wellman et al., ), increased carotid intimal thickness (Pletcher et al., ), and increased coronary calcification (van Trijp et al., ). These findings suggest that binge drinking may be associated with premature CV risk in young adults.…”
mentioning
confidence: 95%
“…Subjects were recruited in 1999 (mean age 12), and follow‐up assessments were measured in 2007 to 2008 (mean age 20) and 2011 to 2014 (mean age 24). Among 24‐year‐old subjects, both monthly and weekly binge drinkers had SBP values 2.61 and 4.03 mm Hg greater, respectively, than nonbinge drinkers (similar BP increases were found in the 20‐year‐old subjects) (Wellman et al., ). Similarly, our group reported that SBP was greater in young adult binge drinkers (120 ± 2 mm Hg) compared with abstainers (114 ± 3 mm Hg), although these differences were not significant (Goslawski et al., ).…”
Section: Binge Drinking and Cardiovascular Conditionsmentioning
confidence: 81%
“…Wellman and colleagues () examined the relationship between BP and current and past binge drinking among young adults (mean age 24). Binge drinking was defined as consuming 5 or more drinks on 1 occasion.…”
Section: Binge Drinking and Cardiovascular Conditionsmentioning
confidence: 99%
“…Data also support that a history of binge drinking in young adulthood is associated with higher BP values. Wellman and colleagues examined the relationship between BP and current and past binge drinking among young adults (men and women, mean age 24 years) 27. Binge drinking was defined as consuming 5 or more drinks on 1 occasion.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, long‐standing differences in drinking patterns between men and women have been converging, such that prevalence rates of binge drinking are rising in women while they remain unchanged in men 36. Studies that have examined the effects of binge drinking on cardiovascular parameters, such as BP have included men and women, but not all of these have determined the potential interaction effect of sex 2, 27. More research is needed to ascertain sex differences in the effects of binge drinking on the cardiovascular system and metabolic parameters in young adult men and women.…”
Section: Discussionmentioning
confidence: 99%